Karya Klasik Pendidikan Islam: Menjelajahi Warisan Intelektual Pendidikan Islam Klasik dan Relevansinya di Era Modern - Krisna Aditiya Wibowo; Najmi Nahdin Afkari; Sugeng Listyoprabowo (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Classical Islamic education is an important foundation that laid the scientific and civilizational groundwork in the Islamic world. However, its relevance is often questioned in the face of modern educational challenges that tend to be secular and instrumentalistic. This article aims to explore the fundamental concepts, highlight the thoughts of major figures, and analyze the relevance of the intellectual heritage of classical Islamic education in the contemporary context. This research uses a library research method with a descriptive-analytical qualitative approach. Data sources are derived from the primary works of classical Muslim thinkers and relevant secondary literature. The results show that: (1) The concept of classical Islamic education is integral, unifying cognitive, affective, and spiritual aspects with an emphasis on adab (ethics), hikmah (wisdom), and tazkiyah al-nafs (purification of the soul). (2) Figures such as al-Ghazali, Ibn Sina, and Ibn Khaldun made monumental contributions by emphasizing moral education, balanced rational development, and the role of education in building civilization. (3) The relevance of this classical thought lies in its ability to offer a holistic educational paradigm that integrates worldly and otherworldly knowledge, prioritizes character formation, and encourages lifelong learning. In conclusion, Muslim Educational Classics provide an authentic and highly relevant philosophical and methodological framework for revitalizing contemporary Islamic education.   Keywords: Classical Islamic Education, Educational Thought, Al-Ghazali, Ibn Khaldun, Educational Relevance